Evolutionary Ecology of Senescence and a Reassessment of Williams' 'Extrinsic Mortality' Hypothesis. (June 2019) - Moorad, Jacob; Promislow, Daniel; Silvertown, Jonathan
Abstract : The evolutionary theory of senescence underpins research in life history evolution and the biology of aging. In 1957 G.C. Williams predicted that higher adult death rates select for earlier senescence and shorter length of life, but preadult mortality does not matter to the evolution of senescence. This was subsequently interpreted as predicting that senescence should be caused by 'extrinsic' sources of mortality. This idea still motivates empirical studies, although formal, mathematical theory shows it is wrong. It has nonetheless prospered because it offers an intuitive explanation for patterns observed in nature. We review the flaws in Williams' model, explore alternative explanations for comparative patterns that are consistent with the evolutionary theory of senescence, and discuss how hypotheses based on it can be tested. We argue that focusing on how sources of mortality affect ages differently offers greater insight into evolutionary processes. Highlights: The evolutionary theory of senescence underpins research in life history evolution and the biology of aging. G.C. Williams predicted that higher death rates select for earlier senescence and shorter length of life. A corollary is that senescence should be correlated with age-independent, or 'extrinsic', mortality. We review the formal, mathematical theory that shows that Williams' verbal model is wrong. Williams' idea has nonetheless prospered because it offers an intuitively appealing explanation for patterns that are widely observed in nature. We offer alternative explanations for the comparative patterns that are consistent with W.D. Hamilton's formulation of the evolutionary theory of senescence. A wider appreciation of how empirical patterns can be explained by the formal evolutionary theory of senescence should stimulate new research.